2015
DOI: 10.1103/physreva.91.053813
|View full text |Cite
|
Sign up to set email alerts
|

Coherent control of light transport in a dense and disordered atomic ensemble

Abstract: Light transport in a dense and disordered cold atomic ensemble, where the cooperation of atomic dipoles essentially modifies their coupling with the radiation modes, offers an alternative approach to light-matter interfacing protocols. Here, we show how the cooperativity and quasi-static dipole interaction affect the process of light propagation under the conditions of electromagnetically-induced transparency (EIT). We perform comparative analysis of the self-consistent approach with ab-initio microscopic calc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The main difficulty is in an exponentially uprising dimension of the Hilbert space in the case of a many particle problem. But this difficulty could be overcome by involving mainly the proximate dipoles in the calculation of the self-energy part similarly to how it was demonstrated for atomic systems in free space, see [7,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main difficulty is in an exponentially uprising dimension of the Hilbert space in the case of a many particle problem. But this difficulty could be overcome by involving mainly the proximate dipoles in the calculation of the self-energy part similarly to how it was demonstrated for atomic systems in free space, see [7,38].…”
Section: Discussionmentioning
confidence: 99%
“…These recent experiments and supporting theoretical studies [33][34][35][36] have shown that light scattering from atoms interacting with the evanescent field of the waveguide mode has important differences from the light scattering from atoms in free space. The effects of Zeeman degeneracy of atomic transition should be taken into consideration for relevant description of the Raman channels, which at present was primary studied in free space [37,38]. The problem becomes more complicated as the strong field confinement provided by the nanofiber imposes an inherent link between the local polarization and propagation direction of light.…”
Section: Introductionmentioning
confidence: 99%
“…By simply adjusting the transmissivity T of the CBS in the CFC loop, the quantum feature of the output entangled state can be manipulated. The presented CFC scheme based on linear optics is able to be applied in other systems for the generation and control of the entangled states, such as nonlinear optical fiber or nanophotonic devices 34 35 36 37 .…”
Section: Discussionmentioning
confidence: 99%
“…We considered here only the transformation of pure states, but the derivation can be straightforwardly generalized towards transformation of an arbitrary initial mixed state ρ(0). The evolution operator U (t, 0) can be found in previous work [20,[22][23][24][25] and is summarized in Appendix A.…”
Section: B Microscopic Description Of the Excitation Decaymentioning
confidence: 99%